IMPLEMENTASI KEBIJAKAN KURIKULUM 2013 DI SMA KESATRIAN 1 KOTA SEMARANG - Mayangsari, Dewi; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
To improve the quality of education, the government formulated a new curriculum policy which is Kurikulum 2013 in order to bring Indonesians become: productive, creative, innovative, affective, through attitude reinforcement, skill and intergrated knowledge. Kurikulum 2013 is the Ministry of Education and Culture Republic of Indonesia’s newest curiculum. Kurikulum 2013 focuses on a comprehension, skill, and charachter building, where students are forced to understand the lesson, to be active in a discussion and a presentation, to have a good attitude and high discipline as well. Kurikulum 2013 legally replaced KTSP that had been applied since 2006. This curiculum has strenght and weakness. Based on the results of research, Kurikulum 2013 is quite right on target. Nevertheless, there are still found some problems associated with the change of KTSP 2006 to Kurikulum 2013 policy in SMA 1 Kesatrian 1 Semarang such as the facilities that are still less in number, the teachers that still use the old method of teaching and there are many classes which teachers are absent yet the students are not given a substitute task. The conclusion of this research is the implementation of Kurikulum 2013 in SMA Kesatrian 1 Semarang is already carried out well but not quite optimum. Apart from a good communication between all parties, they still prefer other occassion beside their priority at school and the internet facility is not quite fast. The advices from this research are school needs to tightnen the rules not only for students but also for teacher and school needs to provide wifi as a facilities.